Bahasa Inggris - Siti Nurfijriyah; Dessy Handa Sari; Mahsun (P3M Politeknik Negeri Banjarmasin, 2026)
This study aims to analyze the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), and Earning per Share (EPS) on stock prices in banking companies listed on the Indonesia Stock Exchange (IDX). The background of this study is based on the importance of stock prices as an indicator of company value that investors pay attention to in making investment decisions. Information contained in financial ratios, such as profitability, capital structure, and earnings per share, can provide signals regarding the condition and prospects of the company, thereby influencing stock price movements. This study uses a quantitative approach with secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange. The research sample was determined using a purposive sampling technique according to predetermined criteria. Data analysis was carried out using multiple linear regression methods with the help of the SPSS program. The results of the study indicate that Return on Equity (ROE) has a negative effect on stock prices, Debt to Equity Ratio (DER) has a negative effect on stock prices, while Earning per Share (EPS) has a positive effect on stock prices. These results indicate that increasing earnings per share provides a positive signal to investors, driving up stock prices. Meanwhile, ROE and DER exhibit an inverse relationship with stock prices in banking companies during the study period. This research is expected to serve as a reference for investors considering financial ratios before making investment decisions, and for companies seeking to improve their financial performance